Tratamento alternativo em gatos acometidos por DITUIF - L.F.A. Trevisan; R.V. Sousa; S.K.V. Bertolucci; O.G. Rodrigues (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2016)
ABSTRACT This report describes two cases of male cats affected by FLUTD (Feline lower urinary tract disease). The first patient had been affected by numerous relapses after passing through various therapeutic treatments and surgical interventions, and was subjected to the alternative protocol after being recommended for euthanasia, the second patient had no history of urinary tract disorders in the past, and was not subjected to any kind of previous treatment. The two patients had a significant improvement in their clinical condition, were not affected by relapses after participation in the alternative design, and were accompanied for about a year after their treatment.